2013
DOI: 10.1167/iovs.12-10959
|View full text |Cite
|
Sign up to set email alerts
|

Retinal Angiogenesis in the Ins2AkitaMouse Model of Diabetic Retinopathy

Abstract: These data indicate that the Ins2(Akita) mouse is a good model for later-onset DR, modeling both early and some late disease signs. Furthermore, this work suggests that this model may be suitable for testing and development of targeted DR therapies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
88
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(96 citation statements)
references
References 48 publications
8
88
0
Order By: Relevance
“…Previous studies with the Ins2 Akita mice have shown a similar trend concerning pro-and anti-angiogenic factors in the retina [22]. These authors did not detect significant differences at 6-months of age but found an imbalance between the expression of VEGF and PEDF in the retinas of 9-months old diabetic mice [22]. It is suggested that the loss of anti-angiogenic factors in the retina might occur at earlier stages of the disease and it might be an event that precedes the overexpression of angiogenic factors.…”
Section: The Ins2supporting
confidence: 69%
See 2 more Smart Citations
“…Previous studies with the Ins2 Akita mice have shown a similar trend concerning pro-and anti-angiogenic factors in the retina [22]. These authors did not detect significant differences at 6-months of age but found an imbalance between the expression of VEGF and PEDF in the retinas of 9-months old diabetic mice [22]. It is suggested that the loss of anti-angiogenic factors in the retina might occur at earlier stages of the disease and it might be an event that precedes the overexpression of angiogenic factors.…”
Section: The Ins2supporting
confidence: 69%
“…In the present study, the expression of VEGF was virtually unchanged in the retina of 6-month old diabetic mice while the expression of VEGF 165 b was highly reduced, comparing with the normoglycaemic mice. Previous studies with the Ins2 Akita mice have shown a similar trend concerning pro-and anti-angiogenic factors in the retina [22]. These authors did not detect significant differences at 6-months of age but found an imbalance between the expression of VEGF and PEDF in the retinas of 9-months old diabetic mice [22].…”
Section: The Ins2mentioning
confidence: 71%
See 1 more Smart Citation
“…In experimental models, similar changes are also seen except for neovascularisation which has never been observed. (Recently it has been reported (Han et al 46 ) that the Akita mouse model of hyperglycaemia develops intraretinal neovascularisation, similar to the intraretinal microvascular abnormalities characteristic of severe diabetic retinopathy in humans. )…”
Section: Diabetic Retinopathymentioning
confidence: 97%
“…Disease onset in this model is at 8 weeks, with an increase in retinal vascular permeability and reactive gliosis. Disease progression continues up to 8 months of age, with a reduction in axons and dendrites of RGCs by 12 weeks, an increase in acellular capillaries at 36 weeks, and an increase in leukocytes in the vascular wall, as a result of inflammation [101,102]. Additionally, a decreased number of cholinergic and dopaminergic amacrine cells [103] is also observed leading to a reduction in the thickness of the IPL and INL [101,104].…”
Section: Mouse Genetic Models Of Drmentioning
confidence: 99%